PV/T water-based cooling in hot climate conditions by using semi-circle baffles - Altharwanee, Hayder; Jurado, Francisco; Vera, David (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
PV/T water-based system using multi-row semi-circle baffles (SCB) is numerically investigated. Experimental validation was carried out in hot climate conditions. Factors associated with heat transfer enhancement, like Nusselt number, pressure drop, friction factor, electrical efficiency, and thermal efficiency, were calculated and discussed to show the impact of SCB on photovoltaic or PV cooling and system performance. Six different magnitudes of Reynolds number (500-4000), and mass flow rate (0.0137-0.0998) L/s at different radiation values were carried out in the simulation. Results indicated that utilizing SCB has an important effect on the PV/T system. In comparison to the smooth channel, the average Nusselt number of the enhanced channel increased by around (31.57-132.18) %, and the friction factor increased by (21.93-95.7) % while the thermal efficiency increased by about (16.34-79.29) %. These results indicate the system’s good performance in terms of photovoltaic panel cooling and power production. PV surface temperature reduced by about (4-20) ℃. The electrical efficiency improved up to 32% and 49% for the smooth and enhanced channels respectively. The cost-benefit ratio (CBR) of the enhanced channel demonstrated that there is no detrimental influence of the pressure drop on the thermal performance.